Relation between precipitation location and antecedent/subsequent soil moisture spatial patterns. Issue 12 (29th June 2017) - Hsu, Hsin; Lo, Min‐Hui; Guillod, Benoit P.; Miralles, Diego G.; Kumar, Sanjiv
Abstract: Recent evidence has shown that relations between soil moisture and precipitation at spatial and temporal aspect are contrary to each other: afternoon precipitation tends to occur at times in which conditions are overall wet and heterogeneous in the morning, but preferentially over those patches that are relatively drier than the surroundings. This study expands the notion of soil moisture‐precipitation spatial coupling by analyzing the preferred precipitation location over a range of different soil moisture patterns. Using global observations of precipitation and observationally constrained evaporative stress estimates, we confirm that relatively drier patches have more chances of receiving rain, but the preference is weakened under wetter soil conditions. During extremely wet times, wet patches have more chances of receiving rain. Moreover, the preference of precipitation to occur on drier soils is stronger when soil moisture conditions are heterogeneous. Such results indicate that the positive feedback mechanism becomes more positive as soil wetness increases and the negative feedback mechanism becomes more negative as soils become drier and more heterogeneous. The strength of these two feedback mechanisms jointly affects preferential precipitation location. Counterintuitively, analysis from 1 day after‐event soil moisture pattern shows that negative soil moisture‐precipitation coupling may in turn further heterogenize soil moisture patterns, because dry patch gets extremely wet with no or less rain in surrounding. Although results here do not necessarily imply a causal relationship, this work contributes to enhancing our understanding of soil moisture‐precipitation spatial coupling and exposes the complex nuances of these land‐atmosphere interactions. Key Points: Afternoon rainfall more frequent over drier patches during dry times, but more frequent over wet patches during extremely wet times Heterogeneity turns negative coupling more negative, and positive less positive Negative spatial coupling tends to enhance the soil moisture heterogeneity rather than leading to homogenously wetter soils on the next day